Analysis of Premium Income and Claim Expenses on Risk Based Capital and profit of Life Insurance Companies in Indonesia for the 2016-2020 Period - Raden Akbar Alif (Dinasti Publisher, 2022)
Literature Research Review of premium income and claims expense on risk based capital and profit of life insurance companies in Indonesia for the 2016-2020 period is a study that aims to test the hypothesis of the influence between each variable used in research that will be investigated by further researchers, within the scope of Management science. Finance. The writing method used in writing this Literature Review article is using the library research method, which is sourced from online media such as Google Scholar, Scribd, online journals and other academics. The results of this Literature Review article are: 1) Premium income has an effect on RBC; 2) Claim expense affects RBC; 3) Premium income has an effect on profit; 4) Claim expense affects RBC; and 5) RBC has an effect on profit. Apart from the 2 variables, namely premium income and claims expenses that affect the RBC and profit variables, there are other variables including investment returns, technical reserves, and underwriting results.